Análisis de los informes epidemiológicos de la fluorosis dental en Colombia en el periodo 2016 – 2019. (2020)
This research work was developed in order to understand the characteristics and analytical results of the epidemiological reports of dental fluorosis in Colombia in the period 2016 to 2019, prepared by the public health surveillance and control institutions in Colombia. The type of research designed was documentary analysis with a methodology of content analysis to thematic nuclei. Epidemiological reports on dental fluorosis in Colombia between 2016 and 2019, prepared by public health surveillance and control institutions in Colombia, were analyzed. The most relevant results show that the methods and strategies that have been used to monitor fluorosis in Colombia have included quantitative records, which provide valuable data for the analysis of this process, such as age ranges, sex, territory. Samples have been used at random or for convenience, according to the monitoring data provided by Sivigila. It is concluded that the increase or decrease in the notifications of cases with dental fluorosis with respect to each period analyzed, depends on the strengthening and decrease of the Sivigila and UPGD surveillance network in all territorial entities, that is, on the disposition of the public institutions of epidemiological control and the contribution of the involved sentinels.